Antimicrobial Activity of the Essential Oil and the Extracts of Kitaibelia balansae Species - Yildirim, Fadime; Memis, Yakup; Ozturk, Ayten; Caliskan, Zerrin; Savran, Ahmet; Abdullah, Meysun Ibrahim (TAYLOR & FRANCIS LTD, 2017)
Essential oils and many components from medicinal plant extracts have been long known for their antimicrobial activity. Essential oils are natural products that are synthesized by the plant and stored in their cells. Essential oils or many of their constituents are in fact effective against a large variety of organisms they can be very well used as alternatives to synthetic chemicals. Kitaibelia balansae Boiss is the only Turkish representative of the genus Kitaibelia that is regularly used as cataplasm herb in traditionally Turkish medicine. In this work the essential oil of the flowers, stems and leaves of K.balansae species, collected from Konya (Turkey) were extracted both by hydro-distillation and Soxhlet and were investigated for their anti-microbial activity. The results showed good activity on the pathogenic microorganisms used. All extracts were analyzed by GC-MS. The antibacterial activities of all the extracts were examined against five Gram-negative, one Gram-positive bacteria and one pathogenic yeast by using disc diffusion method. The results showed the presence of manool, 8, 13-epoxy, 15, 16-dinorlab-12-ene, 8a; 13, 13; 17 depoxy-14, 15-bisnorlabdane and tetrahydroactinidiolide, labda-7,13,14-triene, cis and trans-methyldihydrojasmonate as well as other compounds.
Keywords: Kitaibelia balansae; essential oil; antimicrobial activity; microorganisms; cis and trans-methyldihydrojasmonate; VITIFOLIA; ANTIOXIDANT; Plant Sciences